Managing a transition to green energy sources: The perspectives of energy practitioners in the Southern African Development Community region. - Ramagoma, Justice; Adendorff, Chris (Journal of Energy in Southern Africa, 2016)
The Southern African Development Community (SADC) region has low energy security, exacerbated by electricity power cuts and load-shedding in almost all its member states. Green energy has the potential to contribute to the shortfall in the supply of energy required on the grid network during daily (morning and evening) and seasonal (winter) peak periods. The Statistica 12 program was used to analyse and compare responses between identified groups in the SADC region’s Energy sector. Multivariate analysis of variance and analysis of variance were used to examine associations between variables within the identified categories of respondents, and conclusions were made about six hypotheses. The categories of respondents sampled included: people associated with fossil fuel and renewable energy; people with experience of 1-6 years and more than 6 years; researchers and industry practitioners; practitioners based in South Africa and in other SADC countries; and a category based on practitioners’ positions (junior managers, middle managers, and senior managers) in their respective organisations. The study found that energy practitioners generally support a transition to green energy sources and there is consensus that the uptake of green energy will be slow initially, driven by low costs of fossil-based sources, but the uptake will eventually grow exponentially to a point of driving industries in future. The study recommends that SADC countries prioritise mapping of green energy resources to facilitate the selection of suitable green energy options in order to meet local energy needs and environmental protection. Research and development of suitable green energy storage technologies to overcome intermittency of some green energy sources must be expedited in the region.